Faktor-Faktor Strategis Pendukung Kinerja Sekolah di SMK Kota Surakarta - sugiyarti madyarti (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2015)
This research is a quantitative research design with causal correlation to test the support of the Quality Management System, Student Discipline, Care Teacher and Headmaster of the School Performance in SMK Surakarta. Respondents in this study is the Principal of SMK Surakarta number 49 principals, the sampling technique is taken based on the table Kracjie with α 5% by simple random sampling a number of 44 samples. The technique of collecting data using questionnaires namely Likert type scale in the form of checklist. Analysis of data using multiple linear regression analysis previously performed classical assumption. The results showed that: 1) There is significant support for a quality management system to the performance of vocational schools in Surakarta at 80.7 %, with 2.130 t-test, significance 0.039, p-value 0.05 and correlation of test results obtained by the correlation coefficient 0.807; 2) There is significant support for the discipline of students to the school's performance in SMK Surakarta 78.3 %, with 2.094 t-test, significance 0.043, p-value 0.05 and correlation of test results obtained by the correlation coefficient 0.783; 3) There is a very significant support services teachers and principals on the performance of vocational schools in Surakarta by 80 %, with 2,068 t-test, significance 0.045, p-value 0.05 and correlation of test results obtained by the correlation coefficient 0.800; 4) There is a significant endorsement of the quality management system, student discipline, teacher and principal services on the performance of vocational schools in Surakarta simultaneously by 72 %, with the F-count 37.810, significance 0.000, p-value 0.05, and the value of Adjusted R 0.720 square. The conclusion of this research is the implementation of quality management systems, student discipline, teacher and principal services provide significant support to the performance of vocational schools in Surakarta year 2015.